Danggui Shaoyao San ameliorates Alzheimer’s disease by regulating lipid metabolism and inhibiting neuronal ferroptosis through the AMPK/Sp1/ACSL4 signaling pathway - Gong, Kai; Zhou, Shuang; Xiao, Li; Xu, Mengzhen; Zhou, Yuhe; Lu, Kaihui; Yu, Xin; Zhu, Jiang; Liu, Chuanguo; Zhu, Qingjun (Frontiers in Pharmacology, 2025)
IntroductionAlzheimer’s disease (AD) is a neurodegenerative disorder characterized by cognitive decline; recent studies suggest that neuronal ferroptosis plays a key role in its pathogenesis. Danggui Shaoyao San (DSS), a traditional Chinese medicine formula, has shown demonstrated neuroprotective effects, but its precise mechanisms in AD treatment remain unclear. This study aims to investigate the mechanism of DSS in treating AD by inhibiting neuronal ferroptosis, explore whether DSS alleviates AD by suppressing neuronal ferroptosis via the AMPK/Sp1/ACSL4 pathway.MethodsChemical composition of DSS was identified by LC-MS/MS, followed by network pharmacology to predict targets and pathways. Molecular docking assessed binding affinities between DSS compounds and key proteins (AMPK, Sp1, ACSL4). In vivo experiments on APP/PS1 mice evaluated DSS effects on cognitive function, oxidative stress markers, lipid peroxidation, and ferroptosis-related proteins.ResultsNetwork pharmacology analysis suggested that DSS regulates lipid metabolism and inhibits neuronal ferroptosis via the AMPK pathway. Molecular docking revealed strong binding affinities between DSS compounds and AMPK downstream proteins, Sp1 and ACSL4. In vivo experiments showed that DSS improved cognitive function, enhanced antioxidant capacity, reduced lipid peroxide accumulation, and decreased Fe2+ content in brain tissue. Furthermore, DSS increased the expression of FTH, p-AMPK, and GPX4 while decreasing Sp1 and ACSL4 levels, thereby inhibiting ferroptosis.ConclusionDSS alleviates AD symptoms by suppressing neuronal ferroptosis via the AMPK/Sp1/ACSL4 axis, representing a novel lipid metabolism-targeted therapeutic strategy.